2023
DOI: 10.1021/acs.jced.3c00506
|View full text |Cite
|
Sign up to set email alerts
|

Undecane and n-Alkylcyclohexanes Binary Mixtures: Densities and Speeds of Sound between 288.15 and 333.15 K and Viscosities between 293.15 and 323.15 K at 0.1 MPa

Dianne J. Luning Prak,
Jim S. Cowart

Abstract: The densities, dynamic viscosities, and speeds of the sound of mixtures of undecane with n-alkylcyclohexanes (methyl-, ethyl-, propyl-, butyl-, pentyl-, hexyl-, nonyl-, decyl-, and dodecylcyclohexane) were measured between 288.15 and 333.15 K and 0.1 MPa. Increasing temperature decreased the density, viscosity, and speed of sound. Increasing the concentration of components with higher property values produced mixtures with higher property values for most systems. Excess molar volumes (V m E’s) ranged from −0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Plots showing the deviation of the measured values from literature values for nonane are given in the Supporting Information (Figures S1 and S2). The remaining densities and speeds of sound used in this study have been previously published and can be found in the table of the mixture properties. ,,,, The viscosities of nonane and newly measured values for n -alkylcyclohexanes agree with many of the reported values within the expanded uncertainties of the measurement (Table ). The values for n -decyl and n -dodecylcyclohexanes are higher than those reported from 1953 ref .…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…Plots showing the deviation of the measured values from literature values for nonane are given in the Supporting Information (Figures S1 and S2). The remaining densities and speeds of sound used in this study have been previously published and can be found in the table of the mixture properties. ,,,, The viscosities of nonane and newly measured values for n -alkylcyclohexanes agree with many of the reported values within the expanded uncertainties of the measurement (Table ). The values for n -decyl and n -dodecylcyclohexanes are higher than those reported from 1953 ref .…”
Section: Resultssupporting
confidence: 66%
“…For equimolar mixtures of alkylcyclohexanes and linear alkanes, the V m E s for nonane mixtures are lower than those reported for these alkylcyclohexanes in longer-chain hydrocarbons and higher than V m E s for octane in methylcyclohexane and n -butylcyclohexane, as shown in Figure A at 293.15 K. As the temperature increased, the excess molar volumes for all mixtures decreased. A Redlich–Kister-type expression, eq , was fitted to mixture V m E s according to procedures used in previous work V m E = x 1 x 2 i = 0 n A i ( x 1 x 2 ) i …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations